Analysis of Escherichia coli Microbial Contamination and Total Coliform Bacteria in Refill Drinking Water in Pondok Cabe Ilir Village, South Tangerang City - Puteri Amelia; Ummi Habibah; Ofa Suzanti Betha (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2022)
Water is an essential nutrient for human health. It is important to maintain adequate drinking water intake to prevent dehydration, which can cause hypothermia, dizziness, constipation, and kidney stones. Currently, water-filling stations are an alternative source of drinking water because of limited access to clean water at affordable prices. The purpose of this study was to determine bacterial contamination at a drinking water station in Pondok Cabe Ilir, South Tangerang, Banten, based on Permenkes RI No. 492/Menkes/Per/IV/2010. The study was conducted using the Most Probable Number (MPN) method and the IMViC test, Triple Sugar Iron test, H2S production test, and motility test to identify Escherichia coli. The results showed that one out of five refilled drinking water samples contained Coliform bacteria above the threshold according to Minister of Health Regulation No. 492/Menkes/Per/IV/2010.